2008
DOI: 10.1063/1.2838481
|View full text |Cite
|
Sign up to set email alerts
|

High- and low-field dielectric characteristics of dielectrophoretically aligned ceramic/polymer nanocomposites

Abstract: Polymer/ceramic composites with controlled spatial distribution of fillers are synthesized, and the corresponding changes in their properties are studied. Using dielectrophoretic assembly, we create anisotropic composites of aligned BaTiO 3 particles in silicone elastomer and study their electrical properties as a function of ceramic volume fraction and composite morphology. These structured composites show an increase in the permittivity compared to composites with the same composition and randomly dispersed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 23 publications
6
69
1
1
Order By: Relevance
“…This shows that the addition of nano-TiO 2 can inhibit the injection of the space charges, and the effect of inhibition increases with increasing nano-TiO 2 content. This result is consistent with other studies that showed that nanoparticles are used to improve organic polymers (Tian et al 2011;Tomer et al 2008). 6.67×10…”
Section: Resultssupporting
confidence: 82%
“…This shows that the addition of nano-TiO 2 can inhibit the injection of the space charges, and the effect of inhibition increases with increasing nano-TiO 2 content. This result is consistent with other studies that showed that nanoparticles are used to improve organic polymers (Tian et al 2011;Tomer et al 2008). 6.67×10…”
Section: Resultssupporting
confidence: 82%
“…[19][20][21][22][23][24] When an electric field is applied to an uncured thermosetting polymer, the dispersed particles form chains, which are fixed in place when the matrix is cured. Several studies reporting an increase in the permittivity of a composite material in the direction of these chains have been published, [25][26][27][28][29] However, the effect of the dielectrophoretic alignment on the piezoelectric properties, such as d 33 and g 33 , of piezoelectric particle-polymer matrix composites has not been explored yet, with the exception of one preliminary study. 30 In this paper, the effect of several key processing parameters on these piezoelectric properties and a quantitative coupling of these properties to the structured composites are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several potential applications have been proposed, such as temperature sensors, 4 dielectrics for embedded capacitors, 3,5 and piezoelectric elements for energy harvesting. 6 It has been shown recently that the alignment of PZT equiaxed granulate particles in an epoxy resin results in an improvement of the piezoelectric properties over 0-3 composites with randomly dispersed particles.…”
Section: Introductionmentioning
confidence: 99%